Duplex strengthening via SiC addition and in-situ precipitation in additively manufactured composite materials. (1st May 2022) - Tan, Chaolin; Zou, Ji; Wang, Di; Ma, Wenyou; Zhou, Kesong
Abstract: Additive manufacturing (AM) is flexible to in-situ alloying multi-type powders, which highlights the potential in developing high-performance composite materials with complex geometry. Unlike existing AM-processed metal matrix composites (MMCs) in literature, which are mainly strengthened by the ceramic particles, this work investigates the AM of SiC-reinforced precipitation hardening steel to trigger in-situ precipitation and promote duplex strengthening (ceramic particles + precipitates) in the metal matrix. The effects of SiC content on the densification, microstructure evolution, precipitation kinetics, and mechanical properties are investigated. The relative density of MMCs with 3–12 vol% SiC is higher than 99.4%, and further increasing SiC content deteriorates laser formability and increases defects content dramatically. The microstructure alters from cellular to columnar and then to dendritic structures with increasing SiC addition. Massive nanoprecipitates (e.g., Fe2 Mo and η-Ni3 Ti) are observed in as-fabricated MMCs without heat-treatment, which could have in-situ formed by heterogeneous nucleation at the SiC particles and dislocations. The precipitation kinetics suggests SiC addition increased the nucleation rate of precipitates. Additionally, the hardness of MMCs are enhanced, and the highest yield strength and tensile strength reached about 1.2 GPa and 1.6 GPa in MMCs, respectively. The underlying strengthening mechanisms are the precipitates and SiC particles duplex second-phase strengthening, as well as dislocation strengthening. Highlights: SiC addition affects the precipitation kinetics and accelerates precipitation behaviour. In-situ precipitation promotes duplex strengthening (ceramic particles + precipitates). The achieved tensile strength is at the highest level among a wide range of MMCs.